On Characterizations of General Helices for Ruled Surfaces in the Pseudo-Galilean Space G13-(PART II) - Bektas, M. (Chiang Mai Univ, Fac Science, 2006)
In this paper, we obtained characterizations of a curve with respect to the Frenet frame of Ruled surfaces in the 3-dimensional Pseudo-Galilean space G(3)(1).
Keywords: Ruled surface; General helix